Method of forming a business model of corporate integrated structures and developing algorithms and models of its validity - A. E. Vostroknutov; V. I. Loyko (Новые технологии)
The article presents the results of developing a methodology for forming a business model of corporate integrated structures based on the A. Osterwalder’s approach, supplemented by mathematical models for calculating revenue streams, the number of loyal customers, the depth, breadth and competitiveness of the value proposition. To evaluate the generated data on the business model algorithms and models of its validity have been developed.